Mission statement effectiveness: Investigating managers' sensemaking role - Toh, Seong-Yuen *; Tehseen, Shehnaz *; Mahmoud, A. B.; Cheok, Jason *; Grigoriou, N.; Opute, J. (Emerald, 2021)
Purpose: This study highlights the instrumental role of the mission statement as a tool used by managers to shape value congruence to achieve enhanced employee performance levels. Design/methodology/approach: A variance-based structural equation modelling was used to analyse the data obtained from a sample of 123 managers working in private organisations in Malaysia. Findings: The management sensemaking approach is useful in mission statement research. Managers' involvement in clarifying the mission statement to various firm stakeholders, especially employees, is the strongest predictor of value congruency between employees and the firm, leading to improved levels of employee behavioural performance. Managers can influence value congruency through two processes: (1) guiding and shaping employees' values and (2) adapting the mission statement's contents. Research limitations/implications: Future studies can consider the impact of managerial role modelling on employees' value alignment with the firm in longitudinal studies. Other aspects of alignment offer further research opportunities, for example, HR policy alignment and alignment of marketing and operation strategies with the mission statement. Practical implications: Managers should move beyond treating the mission statement as a management tool. Instead, it is a firm philosophy that reflects managers' words and deeds and exemplifies their philosophical ideals. Originality/value: Despite three decades of research into the relationship between the mission statement and performance, the results have been mixed. Therefore, this study adopts a sensemaking approach to research the mission-performance relationship underpinned by the resource-based view (RBV) theory.